2022
DOI: 10.3390/biomedicines10112854
|View full text |Cite
|
Sign up to set email alerts
|

Membrane Blue Dual Protects Retinal Pigment Epithelium Cells/Ganglion Cells—Like through Modulation of Mitochondria Function

Abstract: Although recent data highlight the greater protective effects exerted by Membrane Blue Dual (MBD), a precise analysis of the mechanisms of action is missing. We examined the effects of MBD with/without polyethylene glycol (PEG) on both human retinal pigment epithelial cells (ARPE-19) and retinal ganglion cells-like (RGC-5) cultured in the presence/absence of ultraviolet B (UVB) treatment on mitochondria function, oxidants, and apoptosis. In ARPE-19/RGC-5 cells either treated or not with UVB, the effects of MBD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 60 publications
(75 reference statements)
0
2
0
Order By: Relevance
“…These data about the harmful effects of EVs from non-healthy subjects are in agreement with those obtained by other groups which demonstrated that the EVs isolated from patients with various diseases—such as atherosclerosis, acute coronary syndrome, or chronic inflammatory diseases—can induce endothelial dysfunction in various in vitro and ex vivo models [ 59 , 60 ], probably due to common pathophysiological mechanisms including impaired vasorelaxation and induction of vascular inflammation through increased levels of adhesion molecules, ROS, and proinflammatory cytokines [ 61 ]. The use of the MTT and JC-1 assay, which are widely adopted to examine cell viability and mitochondrial membrane potential [ 62 ], allowed us to highlight the aforementioned harmful effects of EVs. Indeed, both cell viability and mitochondrial membrane potential decreased in HUVEC.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These data about the harmful effects of EVs from non-healthy subjects are in agreement with those obtained by other groups which demonstrated that the EVs isolated from patients with various diseases—such as atherosclerosis, acute coronary syndrome, or chronic inflammatory diseases—can induce endothelial dysfunction in various in vitro and ex vivo models [ 59 , 60 ], probably due to common pathophysiological mechanisms including impaired vasorelaxation and induction of vascular inflammation through increased levels of adhesion molecules, ROS, and proinflammatory cytokines [ 61 ]. The use of the MTT and JC-1 assay, which are widely adopted to examine cell viability and mitochondrial membrane potential [ 62 ], allowed us to highlight the aforementioned harmful effects of EVs. Indeed, both cell viability and mitochondrial membrane potential decreased in HUVEC.…”
Section: Discussionmentioning
confidence: 99%
“…Mitochondrial membrane potential (ΔψM) is an important parameter of the mitochondrial function used as an indicator of cell health, as previously tested in similar cellular models [ 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 ].…”
Section: Methodsmentioning
confidence: 99%
“…In HUVEC and astrocytes, the viability was examined using the 1% 3-[4,5-dimethylthiazol -2-yl]-2,5-diphenyl tetrazolium bromide (MTT; Life Technologies Italia, Monza, Italy) dye [27,34,35]. To perform this analysis, 50,000 HUVEC/astrocytes/well were plated in 24-Transwells plates in complete medium (DMEM supplemented with 10% FBS).…”
Section: Cell Viabilitymentioning
confidence: 99%
“…We used the JC-1 assay in order to examine the mitochondrial membrane potential of HUVEC/astrocytes, as was the case in previous experiments [27,34,35]. Briefly, HUVEC and astrocytes (50,000 cells/well) positioned in 24-Transwells plates in complete medium were stimulated with plasma for 3 h, as described for the MTT assay.…”
Section: Mitochondrial Membrane Potential Measurementmentioning
confidence: 99%
See 1 more Smart Citation